Genome-Wide Identification and Expression Profiles of Myosin Genes in the Pacific White Shrimp, Litopenaeus vannamei - Zhang, Xiaoxi; Yuan, Jianbo; Zhang, Xiaojun; Liu, Chengzhang; Li, Fuhua; Xiang, Jianhai (Frontiers in Physiology, 2019)
As the main structural protein of muscle fiber, myosin is essential for multiple cellular processes or functions, especially for muscle composition and development. Although the shrimp possesses well-developed muscular system, the knowledge about the myosin family in shrimp is far from understood. In this study, we performed comprehensive analysis on the myosin genes in the genome of the Pacific white shrimp, Litopenaeus vannamei. A total of 29 myosin genes were identified, which were classified into 14 subfamilies. Among them, Myo2 subfamilywas significantly expanded in the penaeid shrimp genomeMost of the Myo2 subfamily genes were primarily expressed in abdominal muscle, which suggested that Myo2 subfamily genes might be responsible for the well-developed muscular system of the penaeid shrimp. In situ hybridization detection showed that the slow-type muscle myosin gene was mainly localized in pleopod muscle and superficial ventral muscle of the shrimp. This study provides valuable insights into the evolutionary and functional characterization of myosin genes in shrimps, which provides clues for us to understand the well-developed muscular system of shrimp.